2014
DOI: 10.1111/and.12380
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between methylenetetrahydrofolate reductase c.677TT genotype and oligozoospermia in infertile male patients living in the Trakya region of Turkey

Abstract: Methylenetetrahydrofolate reductase (MTHFR), the key enzyme of the folate metabolic pathway, has been reported to be five times more active in the testicles compared to other organs in adult mice. The aim of this study was to investigate the relationship between MTHFR c.677C>T and c.1298A>C polymorphisms and infertility in nonobstructive azoospermic and oligozoospermic male patients living in the Trakya region of Turkey. The study population included 75 nonobstructive azoospermic and 62 oligozoospermic, noncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The mechanisms of pathogenesis may involve changes of enzyme structure and mRNA properties that are due to these folate-related enzymes gene polymorphisms[28]. Recent studies have revealed that folate-related enzyme gene polymorphisms were associated with an increased risk of male infertility, particularly in the case of MTHFR gene polymorphisms[1, 29, 30]. Although many studies have reported associations between MTHFR and MS gene polymorphisms and male infertility risk[14, 31], no meta-analysis to date has comprehensively evaluated the relationships of MTHFR and MS gene polymorphisms with male infertility risk in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of pathogenesis may involve changes of enzyme structure and mRNA properties that are due to these folate-related enzymes gene polymorphisms[28]. Recent studies have revealed that folate-related enzyme gene polymorphisms were associated with an increased risk of male infertility, particularly in the case of MTHFR gene polymorphisms[1, 29, 30]. Although many studies have reported associations between MTHFR and MS gene polymorphisms and male infertility risk[14, 31], no meta-analysis to date has comprehensively evaluated the relationships of MTHFR and MS gene polymorphisms with male infertility risk in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Infertility is defined as the failure of a couple to achieve pregnancy after one year of unprotected, regular sexual intercourse, which affects approximately 15% of all couples attempting to conceive a child[1, 2]. In addition to environmental and lifestyle risk factors, genetic causes, such as chromosomal aberrations and single gene mutations, also play important roles in male infertility.…”
Section: Introductionmentioning
confidence: 99%
“…One article [29] had a NOS score lower than five due to the inclusion of selection biases for cases or controls and the lack of adjustment for potential confounders. Two additional eligible studies [30,31] were identified by searching the references of original articles and review articles. In total, 20 articles [11,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] involving 4293 cases and 4507 controls were included in this meta-analysis based on the inclusion and exclusion criteria.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Infertility is a worldwide health problem, which affects an estimated 15% of all couples trying to conceive a child [1,2]. Approximately half of all infertility cases caused by factors related to the male partner [3].…”
Section: Introductionmentioning
confidence: 99%